What Must be Considered when to Perform Consumption Analytics with Facebook Posts? - Nelson Siqueira Rangel Netto; Teresa Cristina Janes Carneiro; Marcos Paulo Valadares de Oliveira; Rogério Antônio Monteiro (BBR: Brazilian Business Review)
This paper aims to discuss and present empirical evidences about whether online recommendations posted on Facebook can be related with consumption intention of its users. Moreover, the perceived reputation of the source of the information, the perceived value of the recommended product, and the perceived risk associated with the product were also considered as possible mediators of this relationship. In this sense, the structural relationship among the variables was assessed through SEM - Structural Equation Modeling. To conduct the study, the Facebook contacts of the author himself were screened using the Snow Ball sampling technique. A total of 402 valid cases were obtained. Among the mediating variables, the one that exerted the least total effect in the relationship was the perceived risk associated with the recommended product. The variable for the consumption intention had a value for R² of 47%, which indicates that the model significantly contributes to the explanation of the influence of the tested factors in the consumption intention of Facebook users. This finding indicates that organizations should invest in monitoring these behaviors and in proactive measures to stimulate consumption.